Cigarette Smoke Amplifies Inflammatory Response and Atherosclerosis Progression Through Activation of the H1R-TLR2/4-COX2 Axis - Barua, Rajat S.; Sharma, Mukut; Dileepan, Kottarappat N. (Frontiers in Immunology, 2015)
Emerging evidence suggest that infection and persistent inflammation are key players in the pathogenesis of atherosclerotic cardiovascular disease (CVD). Although it is well established that cigarette smoke (CS) promotes atherosclerotic CVD, very little is known about the potential impact of the collective effects of CS and intermittent or chronic subclinical infection on atherosclerosis. Our previous studies demonstrated that mast cell-derived histamine and lipopolysaccharide (LPS) synergistically enhance endothelial cell inflammatory response. We further noted that the synergy between histamine and LPS was due to reciprocal upregulation of histamine receptor (H1R) and Toll-like receptor 4 (TLR4) expression and functions. These results suggest that the combined and persistent effects of mast cell mediators and bacterial agents on the vasculature are risk factors of CVD. Our recent data demonstrated that CS extract enhances histamine- and LPS-induced expression of cyclooxygenase-2 (COX-2) in endothelial cells suggesting that CS and mast cell mediators may collectively amplify inflammatory response in the vessel wall. We hypothesize that CS enhances histamine-mediated upregulation of TLR2/TLR4 signaling in the endothelium and promotes progression of atherosclerosis. This article presents our perspective on the modulatory effects of CS and nicotine on the ‘histamine-TLR-COX-2 axis’.